Quantitative lateral-flow immunoassay for the assessment of the cartilage oligomeric matrix protein as a marker of osteoarthritis - Hong, Sung Yub; Park, Yoo Min; Jang, Yo Han; Min, Byoung-Hyun; Yoon, Hyun C. (Biochip journal, 2012)
This study reports a simple and quantitative analytical method for detecting cartilage oligomeric matrix protein (COMP) using a lateral-flow immunoassay (LFI) format. An immuno-chromatographic assay was developed using a gold nanoparticle (AuNP)-conjugated monoclonal antibody (Ab) probe for the quantitative detection of COMP in human synovial fluid (SF). The detection antibody was conjugated with the AuNP (∼30 nm) to enable detection, and the capture antibody was immobilized within a multi-spot pattern in the test zone of a membrane strip. COMP in the human SF binds to the AuNP-conjugated detection antibody, and the COMP-Ab complex then binds to the capture antibody. The immunoassay test can be analyzed by visualizing the test strip with a commercial scanner and an imaging software program. The color density of the multi-spot pattern at the test zone increased in proportion to the concentration of COMP. The developed immunoassay exhibited a dynamic detection range from 0.6 to 20 μg/mL of COMP. The detection limit of the proposed LFI system was approximately 0.2 μg/mL. The test results showed good correlation with those obtained using a conventional enzyme-linked immunosorbent assay (ELISA) to detect COMP. We expect that the proposed immunoassay method, based on the quantification of COMP, is suitable for osteoarthritis diagnosis using SF samples.